Associations of cardiovascular risk factors with survival outcomes in a cancer registration: Findings from the KUMAMON registry. Issue 47 (24th November 2021) - Maki, Yuji; Sueta, Daisuke; Ishii, Masanobu; Yamanouchi, Yoshinori; Fujisue, Koichiro; Yamanaga, Kenshi; Nakamura, Taishi; Tabata, Noriaki; Arima, Yuichiro; Araki, Satoshi; Yamamoto, Eiichiro; Kaikita, Koichi; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Although the relationship between cardiovascular diseases and malignant diseases has recently attracted attention, the associations of cardiovascular risk factors and clinical outcomes in cancer patients remain to be elucidated. We performed a retrospective, observational study that explored the clinical outcomes of patients with cancer or with a history of cancer. We enrolled 30, 706 consecutive adult cancer patients from Kumamoto University Hospital. We investigated mortality and morbidity, including cardiovascular conditions (dyslipidemia [DL]/diabetes mellitus [DM]/hypertension [HT]). The primary endpoint was all-cause mortality. Of the enrolled patients, 9032 patients (29.4%) died within the follow-up period. The Kaplan–Meier analysis demonstrated that in the groups classified according to the number of DL/DM/HT (LDH) factors, the LDH1 and LDH2 groups had a significantly higher probability of the primary endpoint than the LDH0 group ( P  < .001 and P  < .001, respectively), whereas there were no significant differences between the LDH0 group and LDH3 group ( P  = .963). Univariate Cox proportional hazards regression analyses of mortality complemented by the multiple imputation method including various factors demonstrated that the presence of DL in cancer patients was a significant negative predictor of mortality (hazard ratio = 0.79, P  < .01). The all-cause mortality rate did not always increase as the number of LDH factors increased. The present study revealed that the presence of DL is a negative risk factor for all-cause mortality in cancer patients.